Incorporating Environmental Costs into Nigerian Oil and Gas Accounting - Owolabi, Amos Akintola (2015)
This study evaluated the extent of awareness and protective measures by stakeholders of environmental costs in the Nigerian oil and gas industry. It also identified and assessed the environmental factors in the industry that need to be accounted for. These efforts were with a view to developing an accounting model for measuring environmental costs in the industry.